Effects of prior continuous grafting on the growth and cadmium accumulation of Nasturtium officinale cuttings. Issue 1 (2nd January 2021) - Zhong, Lisha; Chen, Shengxiang; Zhang, Fenqin; Lin, Lijin; Liao, Ming'An; Tang, Yi; Zhang, Huifen; Wang, Jin; Lv, Xiulan; Chen, Cheng; Ren, Wei
ABSTRACT: The growth and cadmium (Cd) accumulation of Nasturtium officinale cuttings taken from plants continuously grafted (three times) onto the rootstock of Brassica oleracea were studied in a pot experiment. As the number of grafting events increased, the biomass of the Cd-accumulator N. officinale significantly increased. With the third grafting event, the root and shoot biomasses increased by 369% and 142%, respectively, compared with the control. The photosynthetic pigment content also increased gradually, showing a stable trend after the third grafting event. The superoxide dismutase and peroxidase activities and the soluble protein content reached maximum values with the first grafting event, but the catalase activity showed a gradually increasing trend. The Cd content in N. officinale decreased gradually, but Cd extraction by N. officinale showed an increasing trend. With the third grafting event, the Cd extractions by the roots, shoots and whole plants of N. officinale increased by 190%, 69% and 90%, respectively, compared with the control. Thus, cuttings from continuously grafted N. officinale plants had increased growth and Cd accumulation rates, which improved the phytoremediation capability of N. officinale, with three grafting events being optimum.